PENGARUH OVERCONFIDENCE, HERDING, REGRET AVERSION, DAN RISK TOLERANCE TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI INVESTOR - Timothy Salvatore; Martha Ayerza Esra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Investors often make irrational investment decisions. Decisions are often based on their judgment which is far from rational assumptions. When investors face risky situations, there are some objectivity, emotions, risk tolerance and other psychological factors that usually influence their decision making. The theory underlying this research is Efficient Market Hypothesis and Behavioral Finance. Efficient Market Hypothesis explains how information about a security or stock is used to predict the price of a security or stock in the future so that the resulting return can be predicted. Behavioral Finance studies how psychological phenomena influence financial behavior where there are biases that influence a person's behavior such as overconfidence, herding, and regret aversion. This study uses a judgment sampling by collecting data through questionnaires distributed to 100 respondents who have already invested and are in Jakarta with the help of SPSS 20. Measuring instruments in this study are validity, reliability, average, likert scale, test classical assumptions, and multiple linear regression tests with valid, reliable results, the regression model fulfills the assumptions that the residues are normally distributed, there is no heteroscedasticity, and there is no multicollinearity. The results showed that overconfidence had a positive effect on investor investment decision making, while herding, regret aversion, and risk tolerance did not significantly influence investor investment decision making. Key words : Overconfidence, Herding, Regret Aversion, Risk Tolerance, Investment Decision, Efficient Market Hypothesis